Currency Speculation and the Optimum Control of Bank Lending in Singapore Dollar : A Case for Partial Liberalization - Chan, Kenneth (IMF Working Papers; Working Paper ;, 1996)
The Monetary Authority of Singapore (MAS) has a long-standing policy of controlling bank lending in Singapore dollars to nonresidents and to residents who use the funds outside Singapore. While the control may prevent the internationalization of the Singapore dollar and contain exchange rate volatility, it can hinder the deepening and widening of the financial markets in Singapore. This paper suggests three policy options that would allow traders and investors to borrow Singapore dollars without any restrictions, while making it costly for speculators since their activities can cause exchange rate volatility which arguably imposes external costs to society.